2013
DOI: 10.1063/1.4774341
|View full text |Cite
|
Sign up to set email alerts
|

Threshold criteria for incipient sediment motion on an inclined bedform in the presence of oscillating-grid turbulence

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Here, we report laboratory experiments to investigate the threshold criteria for incipient sediment motion in the presence of oscillating-grid turbulence, with the bed slope inclined at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…The stroke, S, defined as equal to the amplitude of the grid's motion, was varied by changing the radius of the flywheel; strokes of S = 2.5 cm and 3.0 cm were used. These ranges for f and S are in line with those used in previous OGT studies (Hopfinger & Linden 1982;Thompson & Turner 1975;Hopfinger & Toly 1976;McDougall 1979;Wan Mohtar & Munro 2013).…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The stroke, S, defined as equal to the amplitude of the grid's motion, was varied by changing the radius of the flywheel; strokes of S = 2.5 cm and 3.0 cm were used. These ranges for f and S are in line with those used in previous OGT studies (Hopfinger & Linden 1982;Thompson & Turner 1975;Hopfinger & Toly 1976;McDougall 1979;Wan Mohtar & Munro 2013).…”
Section: Methodssupporting
confidence: 74%
“…Measurements of OGT impinging upon a horizontal boundary made by McDougall (1979) exhibited a monotonic reduction of u at low Reynolds number (Re ≡ u /ν ≈ 40; denotes integral length scale), while Hannoun et al (1988) observed amplification of u at higher Reynolds number (Re ≈ 120). Using OGT, measurements showing amplification of tangential turbulent velocities have also been observed at a sharp density interface between two fluids (Brumley & Jirka 1987;Kit et al 1997) and at a sediment boundary (Wan Mohtar & Munro 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, sediment transport in particular the bedload transport rate can be effectively characterized by the shear velocity. However, experimental measurements and theoretical considerations reveal that over the bedforms where the flow is not uniform and the local turbulence varies significantly with bed position, near-bed turbulence is not necessarily correlated with the local mean flow characteristics and thus sediment entrainment may not be characterized by the local bed shear stress or shear velocity [18,23,27,28,33].…”
Section: Introductionmentioning
confidence: 96%
“…Application of the sediment pickup rate function introduced by Miwa and Daido [21] requires estimation of the lift and drag force coefficients, the shear velocity and the critical Shields number s *c , which are all difficult to define over a dune. A recent study that is relevant is due to Mohtar and Munro [23] who examined the sediment threshold over a dune in presence of oscillating-grid turbulence. In their experiments with no mean flow, incipient grain motion was only induced as a result of turbulent fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…This equation is (only) applicable at Z 2.5M, a region considered to reach the state of quasi-isotropic homogeneous turbulence (Hopfinger & Toly 1976). Several studies have employed oscillating-grid turbulence to investigate the threshold criteria for sediment movement, in particular the work of Bellinsky et al (2005) and Wan Mohtar and Munro (2013). This article is set to qualitatively compare the role played by turbulent fluctuations on the overall trend of θ c0 measured by turbulent fluctuations of grid turbulence and vortex ring.…”
Section: Introductionmentioning
confidence: 99%